Evaluation of the efficacy and absorption of a nutraceutical product: pilot study - Tomaino, Laura; Gori, Francesca; Dellanoce, Cinzia; Piontini, Alessandra; Ingenito, Maria Rosaria; Di Donna, Vittoria; Napolitano, Filomena; Soresi, Vincenzo; Vigna, Luisella; Fratter, Andrea (Progress in Nutrition, 2024)
Background and aim: Oxidative stress is a process involved in aging and numerous human pathologies. The aim of this study was to evaluate the safety and efficacy of MITOFAST® in increasing the levels of markers linked to oxidative stress in plasma and red blood cells of healthy subjectsMethods: Prospective pilot study conducted on 22 healthy adult subjects. All participants received two sachets/day for 30 days of a commercial supplement containing a blend of antioxidant micronutrients (Coenzyme Q10, resveratrol, vitamin C, folic acid, and N-acetylcysteine). At enrolment (T0) and after 4 weeks (T1), blood samples were taken to evaluate homocysteine, gluthatione, coenzyme Q10, cysteinylglycine, cysteine, vitamin C, and vitamin E. Furthermore, any side effects reported by the subjects were evaluated. P-value